2020
DOI: 10.1002/cjoc.201900478
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and Divergent Synthesis of Medium‐Sized Lactams through Zinc‐Catalyzed Oxidative Cyclization of Indoly Ynamides

Abstract: Summary of main observation and conclusion An efficient zinc‐catalyzed oxidative cyclization of readily available indoly ynamides has been developed, enabling rapid and practical access to a diverse array of valuable medium‐sized lactams in mostly good to excellent yields with wide substrate scope. In addition, such an asymmetric synthesis has also been explored by employing the chiral substrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…It is worth noting that the related intramolecular oxidative cyclization of indolyl ynamides proceeded smoothly only in the presence of zinc as the catalyst via an intramolecular S N 2′ pathway. 148,150 In the same work, the authors also successfully extended the reaction substrate scope to the tertiary anilines 316 to trap the presumable α-oxo gold carbenes via C−H insertion. As shown in Scheme 131, various substituents were well-tolerated in this oxidative C−H insertion, and the desired α-aryl amides 317 could be formed in good to excellent yields.…”
Section: Nitrones As An Oxidantmentioning
confidence: 98%
See 1 more Smart Citation
“…It is worth noting that the related intramolecular oxidative cyclization of indolyl ynamides proceeded smoothly only in the presence of zinc as the catalyst via an intramolecular S N 2′ pathway. 148,150 In the same work, the authors also successfully extended the reaction substrate scope to the tertiary anilines 316 to trap the presumable α-oxo gold carbenes via C−H insertion. As shown in Scheme 131, various substituents were well-tolerated in this oxidative C−H insertion, and the desired α-aryl amides 317 could be formed in good to excellent yields.…”
Section: Nitrones As An Oxidantmentioning
confidence: 98%
“…The utility of this chemistry was showcased by the formal synthesis of Pfizer’s chiral endothelin antagonist UK-350,926. It is worth noting that the related intramolecular oxidative cyclization of indolyl ynamides proceeded smoothly only in the presence of zinc as the catalyst via an intramolecular S N 2′ pathway. , …”
Section: Gold-catalyzed Carbene-transfer Reactions Based On Pyridine ...mentioning
confidence: 99%
“…In particular, detailed control experiments and density functional theory (DFT) calculations indicated that vinyl cations were most probably involved as key intermediates. Inspired by these results and by our recent study of the development of ynamide chemistry for heterocycle synthesis, , we envisioned that the vinyl cations generated from diyne cyclization might be trapped by borane adducts, leading to valuable organoboranes (Scheme c). Herein, we describe the realization of such a copper-catalyzed diyne cyclization with borane adducts via B–H bond insertion, allowing practical and atom-economic synthesis of various organoborons in generally good yields with a wide substrate scope and good functional group tolerance under mild conditions.…”
mentioning
confidence: 99%
“…This Zn-catalyzed oxidative C–H functionalization was also used for the construction of a series of medium-sized lactams by oxidative cyclization of indolyl ynamides . In addition, such zinc catalysis could be further extended into the oxidative reactions of ynamides with various nucleophiles such as TMSN 3 , TMSNCS, ArOH, and ArSH, allowing efficient and practical synthesis of valuable α-functionalized amides with broad substrate scope and functional group tolerance …”
Section: Transition Metal-catalyzed Oxidation-initiated Tandem Reacti...mentioning
confidence: 99%